PENGARUH KEDISIPLINAN PEGAWAI DALAM IMPLEMENTASI PERWALI NO 15 TAHUN 2016 TERHADAP KEPUASAN PENERIMA HIBAH/BANSOS DI KOTA BOGOR - Heri Susanto; Abdul Muis (Universitas Pakuan, 2017)
AbstractThis study aims to analyze the effect of employee discipline in implementation of Perwali No. 15 Year 2016 to the satisfaction of Hibah/Bansos receipt in Bogor City.The type of research used is associative and quantitative researc. Further, this research also aims to know the causal relationship between variables that is the influence of discipline of regulation, service and attitude in the implementation of Hibah/Bansos fund to receiver's satisfaction in Bogor City Region. Based on the results of analyzed data using multiple regression, it is known that the discipline variable of service that most influence the satisfaction of people who apply for Hibah/Bansos in Bogor City rather than the attitude discipline variable. The Public Welfare Division at Bogor Regional Government is expected to improve its discipline especially in terms of hospitality and greeting in providing services to community who submitted Hibah/Bansos in Bogor City.Keywords: Discipline, Service, Rules, Attitude, Satisfaction